Sejarah Kurikulum Pendidikan Islam di Brunei Darussalam - Aslan Aslan; Suhari Suhari (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2019)
This artilce aimed to analyze of hisotorical Islamic education curriculum in Brunei. This method used field of study or literature. The result showed that Firstly, after Islam came to Brunei, the education system was more in the direction of printing scholars. Secondly, after the arrival of invaders in Brunei, Islamic religious education has experienced dualism, but the curriculum from the Britain has not received a warm welcome. Thirdly, Brunei's independence was inseparable from the role of Britain, so education in Brunei was inseparable from the influence of the educational curriculum of the British nation. Keywords: Islaimic Education Curriculum, Historical Education of Brunnei Darussalam